REDESAIN PACKAGING BOLU KEMOJO “INSAN SUKSES” MAKANAN KHAS RIAU - Hidayat Aydieni pratama, Dra. Jupriani, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Bolu Kemojo Business "Insan Sukses" is one of the home industries located in JL. PEMUDA Gang. PURWO No.19 TAMPAN PEKANBARU, The problem raised was how I redesigned the packaging by making it better, unique, unique and attractive. Through this package redesign, it can have the application of visual identity that can attract the attention of consumers so as to increase sales turnover.This design uses packaging design theory, media, typographic color and layout. Data collection begins with observation, interviews and documentation. Then the data analysis method used is SWOT (Strength, Weaknes, Opportunity, Treatment).This design produces square box packaging that forms like a packaged cake and rectangular box packaging for small size products. In addition to the main media, it is also complemented by a number of supporting media such as small plates, hats, business cards, stickers, polo shirts, aprons, X-benner, chainflag.Kata Kunci : RedesainPackaging, Promosi, Bolu Kemojo “Insan Sukses”